Preliminary Report on the 1994 Season of the Roman Aqaba Project - Parker, S. Thomas (Bulletin of ASOR, 1997)
This report presents preliminary results of the first excavation season of the Roman Aqaba Project (RAP) at the border between the southern end of Wadi Araba and the northernmost extension of the Red Sea. The article includes background, goals, research design, and salient results from excavation of the RAP. Results of the project's regional survey are presented in a companion article by Smith, Stevens, and Niemi (1997). Finally, some preliminary historical conclusions are offered based on this research. The excavation uncovered significant portions of the ancient Nabataean, Roman, and Byzantine city of Aila, which flourished from the first century B. C. to the Early Islamic conquest. It seems clear that parts of the Byzantine settlement continued to be occupied even after construction of the new Islamic walled town in the mid-seventh century A. D. Considerable evidence relating to the economic history of this international commercial port was also recovered.